Salt-induced downregulation of renal aquaporins is prevented by losartan - Della Penna, Silvana L. (2012)
Aims: The purpose of this study was to investigate the expression of aquaporin-1 (AQP-1) and aquaporin-2 (AQP-2) in the renal tubule of rats fed with a high-salt diet and its modulation by the AT1 receptor blocker losartan. Main methods: The experiments were performed in four groups of rats fed for 3 weeks with the following diets: regular rat chow (NS); high-salt (8% NaCl) chow (HS), NS plus losartan (NS-L) and HS plus losartan (HS-L). Losartan (40 mg.kg−1) was administered in the drinking water. Systolic blood pressure (SBP) and renal function were evaluated. The intrarenal levels of angiotensin II (Ang II), TGF-β1, α-smooth muscle actin (α-SMA), endothelial nitric oxide synthase (eNOS), AQP-1 and AQP-2 were determined by immunohistochemistry. AQP-1 and AQP-2 protein levels were measured by western blot analysis. Key findings: A high-sodium diet downregulated AQP-1 and AQP-2 expression levels in the proximal tubule and collecting duct, respectively. The high-sodium diet also induced Ang II, TGF-β1 and α-SMA overexpression and decreased eNOS expression in the renal cortex and medulla. Losartan increased the diuresis and natriuresis, favoring urinary sodium concentration. Additionally, losartan prevented the profibrogenic response, decreasing Ang II, TGF-β1 and α-SMA levels and normalizing AQP-2 expression in the HS-L group. AQP-1 expression was upregulated by losartan in both the NS-L and HS-L groups. Significance: These results show that increased intrarenal Ang II in rats fed with a high-salt diet downregulates renal AQP-1 and AQP-2 expressions. In addition, although losartan increased diuresis and natriuresis, it prevented the downregulation of aquaporins, favoring urinary sodium concentration.